Treatment options for visceral leishmaniasis: a systematic review of clinical studies done in India, 1980-2004. - Olliaro, P; Guerin, P; Gerstl, S; Haaskjold, A; Rottingen, J; Sundar, S (2005)
The state of Bihar in India carries the largest share of the world's burden of antimony-resistant visceral leishmaniasis. We analysed clinical studies done in Bihar with different treatments between 1980 and 2004. Overall, 53 studies were included (all but one published), of which 15 were comparative (randomised, quasi-randomised, or non-randomised), 23 dose-finding, and 15 non-comparative. Data from comparative studies were pooled when appropriate for meta-analysis. Overall, these studies enrolled 7263 patients in 123 treatment arms. Adequacy of methods used to do the studies and report on them varied. Unresponsiveness to antimony has developed steadily in the past to such an extent that antimony must now be replaced, despite attempts to stop its progression by increasing dose and duration of therapy. The classic second-line treatments are unsuited: pentamidine is toxic and its efficacy has also declined, and amphotericin B deoxycholate is effective but requires hospitalisation for long periods and toxicity is common. Liposomal amphotericin B is very effective and safe but currently unaffordable because of its high price. Miltefosine-the first oral drug for visceral leishmaniasis-is now registered and marketed in India and is effective, but should be used under supervision to prevent misuse. Paromomycin (or aminosidine) is effective and safe, and although not yet available, a regulatory submission is due soon. To preserve the limited armamentarium of drugs to treat visceral leishmaniasis, drugs should not be deployed unprotected; combinations can make drugs last longer, improve treatment, and reduce costs to households and health systems. India, Bangladesh, and Nepal agreed recently to undertake measures towards the elimination of visceral leishmaniasis. The lessons learnt in Bihar could help inform policy decisions both regionally and elsewhere.